Amelia, if only - Albertalli, Becky (Harper, an imprint of HarperCollins Publishers, 2025)
"Amelia Applebaum isn't in love with Walter Holland. He just happens to be her favorite moderately famous, chaotically bisexual YouTuber. Who she just happened to invite to prom. (But it's fine. No, for real. If you delete the post, it didn't happen.) Okay, maybe her friends are right: She's slightly parasocially infatuated. But Amelia just knows sparks would fly -- if only she could connect with Walter for real. If only he would host a meet and greet. If only it were just a short road trip away. And if only Amelia could talk her best friends into making it the perfect last hurrah before graduation -- even her newly single, always-cynical, guitar-toting best friend Natalie. One thing's for sure: All roads lead to butterflies. But what if Amelia's butterflies aren't for Walter at all?"--